Influences of feather wear and age on wing lengths of Blue Tits Cyanistes caeruleus. Issue 2 (1st December 2016) - Furness, Euan N.; Furness, Robert W.
ABSTRACT: Although studies of wing length in many bird species show longer wings in adults than in juveniles, and increases in wing length among immature age classes of long-lived birds, evidence for an increase in wing length among adult small passerines is very limited. Previous studies of Blue Tits Cyanistes caeruleus have concluded that adults have longer wing lengths than juveniles but that there is no change in wing length with age of adults, yet the latter conclusion has been based on very limited data. Here we examine wing-length data from a large number of retraps of Blue Tits over a 30-year period at a single site in west Scotland. We found very little evidence for feather wear affecting wing-length measurements during the non-breeding season and, as expected, adults had longer wing lengths than juveniles. However, when comparing individuals caught as both one- and two-year-olds, wing lengths were significantly more likely to increase than decrease. This result has implications for studies of evolutionary biology of Blue Tits, such as survival of individuals in relation to biometrics. It would be interesting to determine whether such age-related increases in wing length are widespread in passerines.